Accumulation of isotope mixture components in a separation cascade; Journal of Engineering Physics and Thermophysics; Vol. 95 - № 2 - Ushakov A. A. Anton Andreevich (2022, 2022)
Numerical investigations have been conducted into the process of separating a multicomponent isotope mixture in a cascade. Regular patterns have been established for the effects of the cascade parameters on the component concentration value in the cascade gas content. Conditions have been identified under which the maximum quantity of the target component is accumulated in the cascade. The investigation results can be used for further study of unsteady processes of accumulating isotope mixture components in a separation cascade.